ESP Instruction in Morocco: A Study of University Students’ Attitudes and Perceptions - Chaimae Farmati; Mohamed Yeou; Bouchaib Benzehaf (Journal of English Language Teaching and Linguistics, 2022)
Language attitude is one of the key factors in foreign language development. In this regard, a plethora of studies has recently provided evidence suggesting that Moroccan students adopt positive attitudes towards learning English as a foreign language for general purposes. These studies focused on students belonging to different streams of study and from different educational levels. However, very few studies have attempted to explore university students’ attitudes toward learning English for specific purposes. Therefore, the present article tries to understand better the status of English for specific purposes in Morocco from different perspectives. It investigates the Moroccan ESP university students’ attitudes toward learning English and attempts to explain the motives behind these attitudes. To meet this end, 125 respondents belonging to various disciplines and from four different Moroccan higher educational institutions completed a survey about the use of English inside and outside school, the importance of this language, and whether these attitudes are driven by instrumental or integrative reasons. Findings revealed that Moroccan ESP university students have positive attitudes towards learning English for specific purposes and want to use it for both instrumental and integrative reasons. In light of these findings, a number of implications are offered.